2013
DOI: 10.1111/eos.12067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of tooth desensitization prior to in‐office bleaching

Abstract: The aim of this clinical trial was to compare tooth sensitivity during and after bleaching with hydrogen peroxide gel following application of GLUMA Desensitizer PowerGel or placebo. Forty-six subjects with sound maxillary incisors and canines were enrolled. Tooth shades were determined by comparison with a Vitapan Classic Shade guide. GLUMA Desensitizer PowerGel and placebo were randomly applied to the labial surfaces of the left or right anterior teeth for 1 min, which were then rinsed and dried. Then, Opale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
3
35
0
3
Order By: Relevance
“…Pal e found a shade change of À3.75 to À4.87 using 28% hydrogen peroxide with a light-emitting diode activation (15). Others have found shade changes from À6.1 to À11 measuring with Vita shade tabs (6,22). While the shade change was less than in other studies, gum chewing did not inhibit the whitening activation because all three groups had similar average shade changes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Pal e found a shade change of À3.75 to À4.87 using 28% hydrogen peroxide with a light-emitting diode activation (15). Others have found shade changes from À6.1 to À11 measuring with Vita shade tabs (6,22). While the shade change was less than in other studies, gum chewing did not inhibit the whitening activation because all three groups had similar average shade changes.…”
Section: Discussionmentioning
confidence: 76%
“…While the shade change was less than in other studies, gum chewing did not inhibit the whitening activation because all three groups had similar average shade changes. Not all studies evaluating shade change use an objective measurement, and many employ the Vita Classical Shade Guide tabs that rely on the human eye (6,11,19,22,27). The use of a spectrophotometer offered an objective measurement of tooth shade (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another clinical trial (MEHTA et al, 2013) compared tooth sensitivity during and after bleaching with hydrogen peroxide gel following application of GLUMA Desensitizer PowerGel or placebo. The results, once again, showed that prebleaching application of the desensitizing agent significantly reduced tooth sensitivity during and after bleaching when compared with treatment with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Although it could be mostly mild or moderate, it is at times so severe that the treatment is discontinued. [4] Enamel is generally considered to be impermeable. Nevertheless, the oxidative free radicals generated from hydrogen peroxide have low molecular weight and are able to denaturize proteins.…”
Section: Introductionmentioning
confidence: 99%